Análisis de la importancia que tiene el biocomercio para la exportación de cacao ecuatoriano Región Costa período 2014 - 2016 - Vicuña Pilataxi, Cynthia Patricia (2018)
Ecuador, producer and supplier of raw materials, promotes new trends in favor of trade; Ecuadorian products located in various parts of the world, countries that show interest in acquiring organic cocoa or fine aroma, considered one of the best on the planet, thanks to its unique and unparalleled flavor and aroma, highly valued for chocolate, gourmet recipes, pastry, cosmetics among others. Today Ecuador advances on the alternative of organic production according to parameters of the biotrade, the main objective is to promote strategies and activities on the use and sustainable conservation of biodiverse areas; in the Ecuadorian Coast there have been registered crops where the production evidences this practice, in 2018 there are 2,216 hectares in the process of transition, that is, reestablishing land possessing chemicals to their original state, with minerals and natural nutrients. The initiative is encouraging for Ecuador, since the cocoa producers have visualized the benefits of organic production within this system called biotrade, there are already awards for quality, generated by the practice of organic production, Cooperativa Fortaleza del Valle in Manabi, it was awarded the 2017 International Cocoa Prize held in the city of Paris.